COVID-19 in patients with glomerular disease. Issue 2 (March 2022) - Turner-Stokes, Tabitha; Edwards, Helena; Lightstone, Liz
Abstract : Purpose of review: Managing patients with glomerular disease during the COVID-19 pandemic has been challenging, as the infection risk associated with immunosuppression must be balanced against the need to control severe glomerular disease that can lead to kidney failure. This review provides an overview of COVID-19 and the effectiveness of SARS-CoV-2 vaccination in patients with glomerular disease. Recent findings: Registry data, although biased towards outcomes of hospitalized patients, suggest that the mortality from COVID-19 is higher in patients with glomerular disease than in the general population. Glucocorticoid use prior to SARS-CoV-2 infection is associated with adverse outcomes from COVID-19. Rituximab significantly attenuates serological responses to both natural infection and vaccination against SARS-CoV-2, although it is not clear whether this leads to adverse outcomes. Case reports of disease flares occurring after vaccination have been reported, but causality in any of these cases has yet to be proven and the absolute risk remains very small. Summary: Patients with glomerular disease represent an at-risk group for severe COVID-19 disease and vaccination is key to reducing this risk. As immunosuppressed patients demonstrate an attenuated response to vaccination, the efficacy of a third primary dose followed by a subsequent booster is being investigated.